ZONA ECONOMICĂ EXCLUSIVĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2009)
The Economic development and the need of protection of maritime environment and of biologic resources have determined various states to claim for a regime of control and sovereign jurisdiction on some special maritime zones of economic protection for the purpose of exploitation and conservation of maritime resources. The establishing of an equitable juridical regime for all states with respect to delimitation of these special zones has led to the necessity of some juridical solutions that would allow a correct right of exploitation for all states in the maritime zones. The key words: exclusive economic zone, treaty, the right of the sea, convention, riparian states.